Fertirrigation for the cultivation of chili (Capsicum annuum) using a drip irrigation system in La Mana - Salazar, Alex (2024)
The research was carried out in the Recta de Vélez Sector, Cotopaxi Province, with the objective of applying fertigation in the cultivation of chili bell pepper (Capsicum annum) using a drip irrigation system; a DBCA design with Tukey at five percent confidence was used; with four treatments (mineral solutions), five replications; evaluating agronomic variables of great importance. As for the results, the mineral solution T1 at 120% obtained superior results in the variables plant height with a value of 85.14 cm, number of leaves with 140.25 units, number of flowers 6.65, equatorial diameter of the fruit with 1.57 cm and number of buds with 10. 90 units, In terms of stem diameter, the T2 mineral solution at 100% had the highest response, with a value of 1.16 cm; in terms of fruit weight, the T4 60% mineral solution obtained a weight of 75.75 g, fruit length of 12.73 cm, number of fruits with 9.30 units and an average yield of 1. 362.50 kg/ha. In the case of the economic analysis, the treatment with the 60% solution had a profitability of 35%, which means a production of 1,362.50 kg/ha, yielding a value of US$ 3,319.38 per hectare.